Dual-mode multicolored photonic crystal patterns enabled by ultraviolet-responsive core-shell colloidal spheres. (January 2018) - Gao, Zewen; Huang, Chao; Yang, Dian; Zhang, Hanbing; Guo, Jinbao; Wei, Jie
Abstract: In this study, we developed a new kind of dual-mode multicolored photonic crystals (PCs), which could be used as a new type of dye, and achieved multicolored patterns. This kind of PCs can exhibit not only distinct structural colors due to Bragg's law of diffraction but also non-structural colors due to fluorescence. We used ultraviolet (UV)-responsive colloidal spheres synthesized by polymerization of semi-continuous emulsions to assemble the PCs. In this synthesis, the fluorescent precursors with carbamate groups were locally restricted to the shell of prepared spheres. UV irradiation can induce photo-decomposition of the carbamate groups in the fluorescent precursors, generating amino groups in the process. This process allowed the assembled PCs to exhibit fluorescence through treatment with fluorescamine. We prepared two-dimensional (2D) multicolored photonic patterns of different sizes, with both reflection and fluorescence modes. These patterns were prepared either by vertical deposition under selective UV irradiation, or by spray coating. In addition, we fabricated three-dimensional (3D) multicolored photonic patterns using 3D templates, as well as through spray coating. The results expand the concept of responsive PCs, and offer potential applications for multicolored photonic crystal patterns (PC patterns) in the field of optical storage, color displays, and anti-counterfeiting. Graphical abstract: Highlights: We designed and fabricated photonic crystals assembled by ultraviolet-responsive core-shell colloidal spheres. The photonic crystals could exhibit fluorescence after UV irradiation and subsequent reaction with fluorescamine. We created 2D and 3D multicolored photonic crystal patterns, via either selective UV irradiation or spray coating.